Derechos humanos e izquierdas en Argentina. Entre la revolución y el paradigma humanista - Vera Carnovale (Nuevo mundo - Mundos Nuevos, 2020)
Kirchnerist policy on memory and justice has stirred up critical voices to the human rights movement. This rejection points, on the one hand, to the consecrating narrative of the seventies experience that seems to have been imposed in the public space and, on the other, to a postulated co-optation of the human rights movement by the left. This article proposes to think about the historical links between human rights and the left, both from the unresolved tension between the revolutionary and the humanist tradition and from the predominant contribution of the revolutionary militancy, especially that of the 70s, to the conformation of the human rights movement in Argentina.